As deficiências conceituais por trás dos erros - Lima, Elson Nascimento (2013)
This study aims to analyze the conceptual shortcomings through the mistakes made by the candidates/teachers in addressing the issue of discursive question 2 of the Exame Nacional de Acesso ao Mestrado Profissional em Matemática em Rede Nacional - PROFMAT 2013 in Sergipe, which statement is as it follows: DISCURSIVE QUESTION 2 Decide whether each of the two following statements is true or false, explaining your reason for choosing it. (A) |a - b| = ||a| - |b||, for any real numbers a and b (B) |a + b| = |a| + |b|, for any real numbers a and b It is not only the mere cataloging errors, but it is also a reflection on the shortcomings in content concepts that are part of the curriculum of the Elementary and High School levels. We analyzed the solutions of 180 candidates/teachers , we cataloged the major mistakes, we researched on the theory of the role of errors in learning process, and through what we observed, we realized, among other results, that the students of Teacher´s Degree in Mathematics (Licenciatura em Matemática) in Sergipe have an unsatisfactory training.